Orcinus Orca in Captivity: Behavioral and Physiological Effects - Wu, Yaohui (Transactions on Environment, Energy and Earth Sciences, 2024)
The captivity of orcas has been a controversial topic for decades, with significant ethical, behavioral, and physiological concerns. While marine parks promote orca shows as educational experiences, orcas often display abnormal behaviors, including stereotypic behaviors and social disruptions, as well as experience a range of health problems, such as dorsal fin collapse and compromised immune systems. This article examines the history of orca captivity, the profound impact it has on their natural behaviors and health, and the latest research and case studies that illustrate the detrimental effects of such confinement. By exploring alternatives to captivity, such as marine sanctuaries and rehabilitation programs, we can move towards more ethical solutions that prioritize orca welfare. This article also addresses the growing body of scientific evidence calling for the end of orca captivity in favor of humane alternatives that align with conservation and public education efforts. Emerging alternatives, such as marine sanctuaries and rehabilitation programs, provide more humane options that allow orcas to live in the environments that are closer to their natural habitats. By encouraging public education through innovative technologies like virtual and reality, the article emphasizes the importance of shifting away from traditional captivity. Ultimately, this paper advocates for the future welfare of orcas, promoting conservation efforts and ethical practices that respect these remarkable marine mammals.